Przekład i przestrzenie lektury - Scott, Clive (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The author discusses relations between the original and translation in terms of imaginary spaces. Target text is understood here as one of the possible images of the source text, from the perspective which could not be accessible to the original. In accordance with the concept presented here, artistic translation can be not so much reconstructed, as conceptually constructed, in the manner of a cubist object. Acts of creative reading are commented on by the author with examples of his own experimental translations from contemporary French poetry.